A Retrospective Observational Study of Adverse Reactions Associated With Intravenous Immunoglobulin Infusion - Kato, Hidefumi; Hayashi, Megumi; Ohashi, Wataru; Yamaguchi, Takamasa; Tanaka, Satomi; Kozono, Ayumi; Gao, Siqiang; Katai, Akiko; Niwa, Reiko; Matsuo, Tomohito; Ishiyama, Kazuki; Ando, Takanori; et al. (Frontiers in Immunology, 2021)
Background: Although intravenous immunoglobulin (IVIG) therapy is generally safe and well tolerated, adverse reactions (ARs) do occur. The majority of these ARs are mild and transient. Risk factors for ARs associate with IVIG infusions are not well established. This study investigated possible risk factors influencing the occurrence of IVIG-associated ARs. Study design and Methods: This was a retrospective observational analysis of data accumulated over 5 years, including patient demographics, clinical condition, pre-treatment medications, IVIG doing regimens, number of IVIG infusions, and any ARs. Results: ARs were associated with IVIG in 4.9% of patients. By univariate analyses, ARs correlated with female sex, adult age, high dose IVIG, and autoimmune disease. Multivariate logistic regression identified three statistically significant of risk factors: being female (p=0.0018), having neuromuscular disease (p=0.0002), and receiving higher doses of IVIG per patient body weight (p<0.001). Conclusion: Neuromuscular disease emerged as one of the significant factors for ARs to IVIG.